Digital Marketing Innovation to Enhance Sheep (Ovis aries) Marketing Performance: A Case Study at PS Tunas Muda, Tuban Regency - Elsa Afifatun Nur Rohmah afifa; Joko Gagung Sunaryono; Hana Nur Eritrina; Fitria Nur Aini (UNIVERSITAS ISLAM LAMONGAN, 2026)
This study aims to analyze the utilization and optimization of TikTok and Facebook as Digital Marketing strategies to increase the sales volume of sheep (Ovis aries) at PS Tunas Muda Farm, Tuban Regency. The study was motivated by the use of conventional marketing methods, which limited market reach and resulted in suboptimal sales volume. This research employed a quantitative descriptive method using primary and secondary data sources. Data were collected through observation, interviews, and documentation. The data were analyzed using descriptive analysis, a One Way ANOVA test to determine differences in sales volume before and after the implementation of Digital Marketing, and a business feasibility analysis including production costs, revenue, profit, R/C Ratio, B/C Ratio, Break Even Point (BEP), and Return on Investment (ROI). The results indicate that the implementation of Digital Marketing through TikTok and Facebook increased promotional reach, Engagement, and sales conversion. However, the One Way ANOVA test showed a significance value of 0.620 > 0.05, indicating that there was no statistically significant difference in sheep sales before and after the implementation of Digital Marketing. Although there was a numerical increase in sales volume after the strategy was applied, the increase was not statistically significant. Financial analysis shows that the sheep farming business at PS Tunas Muda is feasible to develop, as indicated by an R/C Ratio of 1.37 (>1), a B/C Ratio of 0.37 (>0), a BEP production level of 42 sheep, a BEP price of IDR 1.145.840, and an ROI of 37%, reflecting a positive rate of return. The marketing margin analysis also indicates a more efficient profit distribution after the optimization of digital promotion. Thus, the implementation of Digital Marketing through TikTok and Facebook effectively expanded market reach and supported business feasibility, although it did not produce a statistically significant increase in sales volume.